Internship program at Museum Gedung Sate for student professional experience - Dita Lestari (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
The development of student competencies does not stop within the classroom but must be strengthened through direct exposure to the professional work environment. Universities play a strategic role in facilitating students' access to professional experience as preparation for independent careers after graduation. This internship program aims to enhance students’ competencies, including both soft skills and hard skills, through active involvement in a professional workplace. The internship spanned 40 working days at the Gedung Sate Museum, an institution dedicated to preserving local history and culture. The program was designed to provide practical work experience beyond academic learning by engaging students in roles such as museum educators, visitor receptionists, audiovisual assistants, and social media content managers, particularly in creating Instagram captions. Through this internship program, students gained valuable experience, knowledge, and skills, including effective communication, interpersonal and customer service, information technology proficiency, and an understanding of digital marketing strategies and online communication. Furthermore, students applied the theoretical knowledge acquired during their university studies in a real-world context, actively contributing to the preservation and promotion of local history and cultural heritage through educational and creative activities at the museum.   Abstrak Pengembangan kompetensi mahasiswa tidak berhenti pada proses pembelajaran di ruang kelas, tetapi perlu diperkuat melalui pengalaman langsung di dunia kerja. Universitas memiliki peran strategis dalam memfasilitasi mahasiswa agar memperoleh pengalaman profesional sebagai bekal kemandirian setelah lulus. Program pemagangan ini bertujuan untuk meningkatkan kompetensi mahasiswa, baik soft skill maupun hard skill, melalui keterlibatan langsung di lingkungan kerja profesional. Kegiatan pemagangan dilaksanakan selama 40 hari kerja di Museum Gedung Sate sebagai salah satu institusi pelestarian sejarah dan budaya. Program ini dirancang untuk memberikan pengalaman kerja nyata di luar bangku kuliah melalui berbagai peran, antara lain sebagai edukator museum, resepsionis layanan kunjungan, pengelola audio visual, serta pengelola konten media sosial khususnya pembuatan caption Instagram. Melalui pelaksanaan magang ini, mahasiswa memperoleh peningkatan pengetahuan, pengalaman, dan keterampilan, seperti kemampuan komunikasi efektif, keterampilan interpersonal dan pelayanan publik, penguasaan teknologi informasi, serta pemahaman strategi pemasaran digital dan komunikasi daring. Selain itu, mahasiswa mampu mengaplikasikan ilmu yang diperoleh selama perkuliahan secara kontekstual dan berkontribusi aktif dalam upaya pelestarian sejarah serta budaya lokal melalui peran edukatif dan kreatif di museum. Kata Kunci: Museum Gedung Sate; pengalaman profesional; program magang